EVALUASI KEBIJAKAN PENANGANAN DAMPAK PERTAMBANGAN TIMAH RAKYAT DI KECAMATAN DAMAR, KABUPATEN BELITUNG TIMUR - , ROSITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The activity of tin mining in Belitung Island has started since the Dutch colonial period. As Time goes by, mining activity cause the impact on physical, social and economic aspect. Since most of them are the negative impact, so thatâs what made The Government of East Belitung District make the policy. These policies aim to solve and reduce the impact, so the impact wonât be greater. Therefore, this research aimed to evaluate the policies of the local tin mining that made by the local government of East Regency The researchâs method is the descriptive qualitative method. This method combines some datas, the primary data, secondary data, and the data that obtained in the field through questionnaires and interviews. Interviews were conducted to the local government, the subdistrict Damar Society, and people who work as miners. The research sites include 5 (five) villages, they are Air Kelik Village, Mempaya Village, Burung Mandi Village, Mengkubang Village and Sukamandi Village. In this research, evaluation techniques use the evaluation concept of William Dunn, Public Policy Analysis. The tin mining activity by local community cause some impacts for physical, social, and economic aspectThe Local Government policies that evaluated in this research is mined land reclamation policy , the policy of \" Good Mining Practice \" training and zoning policy of local community mining or as known as âWilayah Pertambangan Rakyatâ ( WPR ).From the results of the evaluation , a total of 51 respondents considered that the local government still doesnât accompany in field directly to do reclamation, so there are still many open-mined land left. A total of 72 percent of the population considered that the WPR policy still can not resolve the problem of land disputes. Additionally This WPR policy is not effective because the referenced land use document, The Urban Land Use Plan of The East Belitung Regency is still not official for public publishing. The local community still doesnât in the field what they get on \" Good Mining Practice \" training. It is caused of people had been already familiar with the common pattern and process of tin mining. So from the evaluation process, the local government policies are still not effective. The participation of local community and cooperation of local government and private sector is the success key on the policy implementation.